2020
DOI: 10.24843/atbes.2020.v04.i02.p06
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Growth Rate (Eucheuma cottonii) in Monoculture and Co-Culture Cultivation Systems in Coastal area of Pandawa Beach, Bali

Abstract: Seaweed is one of Indonesia's fishery commodities with great potential to be cultivated, the condition of seaweed produced in Indonesia is not optimal yet. This can be seen from the low productivity of seaweed in Indonesia which is caused by the low growth rate. The growth rate of seaweed can be supported by proper planting techniques and cultivation methods. Seaweed farmers generally use planting techniques and traditional cultivation methods called the monoculture system, which is planting one type of plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
0
2
Order By: Relevance
“…The SGR value in this study was lower than the results of Breanita's research [15] on seaweed with SGR values ranging from 3.42-4%/day at abalone densities of 10 and 30 individuals. Ice-ice disease attack affects the low SGR value of cultured seaweed and was thought to be one of the causes of the difference between the results of this study and previous studies, as explained by Yulianto [16] The results of the statistical analysis of seaweed weights in monoculture and polyculture, showed that the value of sig was 0.049 ≤ 0.05, which means that there was a significant difference between the treatments of monoculture and polyculture cultivation.…”
Section: Figure 3 Spesific Growth Rate Of Seaweedcontrasting
confidence: 89%
See 1 more Smart Citation
“…The SGR value in this study was lower than the results of Breanita's research [15] on seaweed with SGR values ranging from 3.42-4%/day at abalone densities of 10 and 30 individuals. Ice-ice disease attack affects the low SGR value of cultured seaweed and was thought to be one of the causes of the difference between the results of this study and previous studies, as explained by Yulianto [16] The results of the statistical analysis of seaweed weights in monoculture and polyculture, showed that the value of sig was 0.049 ≤ 0.05, which means that there was a significant difference between the treatments of monoculture and polyculture cultivation.…”
Section: Figure 3 Spesific Growth Rate Of Seaweedcontrasting
confidence: 89%
“…The average of abalone survival rate was 72.7%. The survival value of abalone in this study was lower than that of Breanita [15] in Pandawa Beach with abalone densities of 10 and 30 individuals with an average abalone survival value of 96%. Followed by a decrease in weight gain in polyculture cultivated seaweed.…”
Section: The Abalone Survival Rate (Sr) Of Abalonecontrasting
confidence: 69%